Is the six-minute walk test still reliable compared to cardiopulmonary exercise test for exercise capacity in children with congenital heart disease? - Qu, Jiangbo; Shi, Hui; Guo, Yugong; Chen, Xinxin; Xiao, Xuwen; Zheng, Xiaojuan; Cui, Yanqin (Frontiers in Pediatrics, 2022)
Objectives: We aimed to assess the validity of the six-minute walk test (6MWT) to reflect the functional capacity of children with congenital heart disease (CHD), evaluate a possible correlation between the 6MWT distance with cardiopulmonary exercise test (CPET) variables, as well as to find a cutoff value to stratification the physical fitness in this population. Methods: We enrolled 459 children with CHD, 6-18years old, who performed a complete CPET and 6MWT on the same day in a cross-sectional observational study. Correlations between variables of CPET and six-minute walking distance (6MWD) were analyzed and cutoff values of 6MWD were identified for the classification of the physical fitness in the population. Results: The mean distance ambulated during the 6MWT was 577.98±64.87m, 590.41±64.51m for boys, and 562.04±61.91m for girls (p<0.001). Both VO2max and %predicted VO2max showed a correlation with the 6MWT distance (r=0.35, p<0.001 and r=0.51, p<0.001, respectively), and an inverse correlation was found between VE/VCO2 slope and the 6MWT distance (r=−0.31; p<0.001). There appeared to be a linear association between 6MWD and VO2max up to a 6MWD of approximately 600 m. We divided the population into 4 subgroups (boys <130cm; boys ≥130cm; girls<130cm; girls≥130cm), and get the cutoff values (553.5m, 617m, 548.5m, 586.5m) respectively equivalent to 80% of predicted VO2max. The 6MWT distances of another 102 patients were applied for external verification of the cutoff values. Conclusions: Our study provided evidence on when a 6MWT should be considered as a convincing complementary test in the pediatric population with CHD and explored the classification of exercise tolerance using a 6MWD value. The cut-off values for 6MWD may be qualified as an intervention target for exercise rehabilitation.